New Business Strategy and Implementation During Covid 19 for PO Primajasa (The Indonesian Journal of Business Administration, 2020)
PO Primajasa has been operating since 1991 and was founded by Amir Mahpud. It serves passenger to travel in DKI Jakarta, West Java, and Banten area. The company is originated from Tasikmalaya, and has close relation with PO Mayasari Bakti. Now PO Primajasa is the market leader in those areas for mainstream market.Company growth for the past 5 years can be described as stagnant growth. Second generation, Tiar Karbala, has taken over half of the business since 2018. The main objective is to double the business in 2025. Amir Mahpud believe that transportation company is the most important aspect to run the economic wheels so the demand of transportation will be much higher in the future. Company needs a new breakthrough to get more passengers and provide new services in the near future.Covid 19 has a serious impact for transportation business. As government release a regulation called Pembatasan Sosial Berskala Besar (PSBB) which limited people to commute between city. This regulation force company to shut the operation for almost 3 months. As a company owner, Amir Mahpud urges the company to comply the regulation to put safety and healthy as company priorityNow company start operating but with tight health protocol and can only accommodate maximum 50% from total passenger.To find the best solution for this issue, this paper will focus on how company and business has been going on since beginning. Internal analysis will be explained in this research with value chain analysis and business model canvas as framework. While external analysis will use value proposition canvas and porter 5 forces as the main framework. Later on, it will decide the business decision to find the best solution to overcome all the problems.This final project will focus on analysis to know more about the company and the business. Further it will defines the best solution growth during Covid-19 pandemic. Company has urgency to have more growth after pandemic has done because it had stopped operating for almost three months during pandemic. This paper will provide solution and implementation for Primajasa to improve the business in the future.Keywords: Business Strategy, Transportation Industry, Strategy during Covid-19